EKSAMINASI TERHADAP TINDAK PIDANA PENIPUAN PADA PENGADILAN NEGERI KUDUS DALAM PUTUSAN PERKARA NO. 124/Pid.B/2019/Pn.Kds - Nugroho, Haryo Yudhistira Hamengku; Astuti, Pudji; Ahmad, Gelar Ali (NOVUM : JURNAL HUKUM)
Developers are prohibited from selling plots of land, according to Article 1 number 17 of Law no. 1 of 2011 concerning Housing and Settlement Areas defines mature land plots as "a plot of land that has been prepared for a house in accordance with the requirements for use, control, land ownership, detailed spatial planning, as well as building and environmental planning." In connection with the provisions regarding selling mature land lots according to the explanation of Article 146 paragraph (1) of Law no. 1 of 2011 concerning Housing and Settlement Areas states that mature land lots are "an activity of a legal entity that deliberately only markets mature land lots to consumers without building houses first". Selling mature land lots, according to Article 146 of Law no. 1 of 2011 concerning Housing and Settlement Areas that "legal entities that build Ready-to-Build Environment (hereinafter abbreviated as Lisiba) are prohibited from selling mature land plots without houses", the prohibition is aimed at developers who build housing which are prohibited from selling mature land lots without houses. Taking into account the description, the issues discussed were what was the basis for the consideration of the public prosecutor to charge ADY PRIYO LEKSONO with Article 378 of the Criminal Code in cases that were decided by decision Number 124 / Pid.B / 2019 / Pn Kds and Is Article 154 of Law Number 1 Year 2011 concerning Housing and Housing not worthy of being accused.